Factores predisponentes para la adquisición de Candida albicans en el tracto urinario de pacientes adultos hospitalizados en el Hospital Universitario de Maracaibo durante el periodo 1999-2001 - Colmenares Berkis; Mesa C Luz M; Magaldi Sylvia; Beltrán-Luengo Haydee; Pineda Maritza; Colmenares Ciolys; Villalobos Rafael; Calvo M Belinda (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2006)
Abstract: For the purpose of studying the predisposition factors in patients in the acquisition of Candida albicans in the urinary tract, retrospective research was undertaken in the University Hospital in Maracaibo from 1999-2001. For such a purpose a sample of 53 patients was taken: 28 showing the presence of Candida albicans (Ca+) and 25 that did not show it (control), with an average overall age of 42. The variables studied were sex, time of hospitalization (TH), permanence in an intensive care unit -UCI- (IU), use of bladder catheter (SV), bladder catheter usage time (TCSV), use of antibiotics (UA), duration of the use of antibiotics (TUAB) and number of antibiotics used (NAB). The data was registered in a questionnaire type instrument. The statistical analyses of the results showed that in Ca+ patients, the variables: TH, TCSV, TUAB, NAB, IU and female (sex), were more frequent than the averages of each one of these variables in the Ca- group. The discriminative analysis for the same variables allowed for the establishment of statistically significant relation with variables TCSV, TUAB and NAB; although the last variable did not have any influence in the model when the discriminative equation was analyzed. The Jiquare test indicated that there was dependence for the feminine sex, TCSV was greater at 10 days, NAB was greater or equal to 2, TUAB was greater at 14 days. Early removal of the bladder catheter and the adequate use of antibiotics during hospitalization, are practices that help to prevent the acquisition of C. albicans in hospitalized patients. Resumen: Con el fin de estudiar los factores que predisponen al paciente para la adquisición de Candida albicans en el tracto urinario, se realizó una investigación de tipo retrospectiva en el Hospital Universitario de Maracaibo durante el período 1999-2001. Para tal fin se tomó una muestra de 53 pacientes: 28 que mostraron la presencia de Candida albicans (Ca+) y 25 que no la mostraron (control), con una edad promedio de 42 años. Las variables estudiadas fueron sexo, tiempo de hospitalización (TH), ingreso a UCI (IU), uso de sonda vesical (SV), tiempo de colocación de sonda vesical (TCSV), uso de antibióticos (UA), tiempo de uso de antibióticos (TUAB) y número de antibióticos (NAB). Los datos se registraron en un instrumento tipo cuestionario. Los análisis estadísticos de los resultados mostraron que en los pacientes Ca+ las variables: TH, TCSV, TUAB, NAB, IU y sexo femenino fueron más frecuentes. El análisis discriminante de las variables estudiadas permitió establecer relación estadísticamente significativa con las variables TCSV, TUAB y NAB, aunque esta última variable no tiene influencia en el modelo al analizar la ecuación discriminante. La prueba de Ji-Cuadrada indicó que hubo dependencia entre el sexo femenino, TCSV mayor a 10 días, NAB mayor o igual a 2, TUAB mayor a 14 días. La remoción temprana de la sonda vesical y el adecuado uso de antibióticos durante la hospitalización, como medidas de prevención podrían evitar la adquisición de C. albicans en la orina de pacientes hospitalizados.